Sensitivity of the nested-polymerase chain reaction (PCR) assay for Brugia malayi and signi®cance of `free' DNA in PCR-based assays - Cox-Singh, J.; Pomrehn, Andrea S.; Wolfe, Nathan D.; Hasan, A. Rahman; Huong-Ying, Lu; Balbir, Singh (Elsevier Ltd., 2000)
The blood filtration method was used as the gold standard to determine the detection level of simple blood-spot sampling and nested-polymerase chain reaction (PCR) for Brugia malayi. Of 100 samples, 48 were filtration-positive. Of these, 26 had microfilaria counts that were low enough (<1–29 microfilariae/ml) to accurately assess the limit of detection by nested-PCR. Nested-PCR consistently detected B. malayi DNA in samples with ≥10 microfilariae/ml. Post-filtration, microfilaria-depleted, blood-spots from microfilaria-positive samples were screened by nested-PCR and B. malayi specific ‘free’ DNA was detected in 51.7% of these samples. There was no evidence for ‘free’ DNA in microfilaria-negative individuals from this endemic community.